Faktor Makro dan Mikro yang Mempengaruhi Penerimaan Retribusi Pelayanan Pasar di Kabupaten Kediri - Sururin Khariroh; Arisyahidin Arisyahidin; Imam Baehaki (Universitas Islam Kadiri, 2023)
The implementation of regional autonomy encourages autonomous regions to be independent in financing their regional finances. One of the regional financial sources is PAD (Regional Origin Income) and market service levies. Market service levies is a type of income that can be increased and its potential can be explored. The aim of this research is to analyze the macro and micro factors that influence the receipt of market service fees. The independent variables from macro factors are economic growth and inflation, while the independent variables from micro factors are tariffs, quality of service level and knowledge and understanding of traders. The research method used is a quantitative analysis method. The research location was carried out at Gringging Market, Kras Market and Bendo Market with total of 98 respondents. The data collection technique used in this study is randomly distribute questionnaires to traders in the 3 markets. The results of this study indicate that economic growth, inflation, tariffs, quality of service level and knowledge and understanding of traders simultaneously influence market service retribution acceptance. However, partially, economic growth, tariffs, quality of service level and knowledge and understanding of traders have a positive effect on acceptance of market service fees, while inflation partially has no effect on acceptance of market service fees.